Knowledge of river dynamics as a tool for planning. Case Volcán River, Buenos Aires, Puntarenas, Costa Rica - Segura-Serrano, Laura (2014)
Costa Rica has a high water supply and an extensive hydrographic network. Nevertheless studies of ri-vers dynamics are not consider as a tool for decision making in urban planning. This has led to negative consequences on environmental risks. The community of Volcán, Buenos Aires, Puntarenas, Costa Rica wanted to validate the risk map of the National Emergency Comission (CNE) though a technical study. Through the project “Management Plan river basin Volcán” we were able to study the hydraulic response of the river Volcán to different flow data. The study revealed which were the areas with the greatest flood threat. This information is available to assist the decision making of the Town Hall of Buenos Aires and the community.